A brief history of Northern Kentucky - Webster, Robert D., 1958- (South Limestone Books, an imprint of the University Press of Kentucky, 2019)
From the arrival of the first European settlers in the late 1700s to the building of the Ark Encounter at Williamstown in 2016, Northern Kentucky's overall landscape and population has changed in dramatic fashion. Once a sparsely-populated and rugged wilderness with beautiful creeks, broad rivers, and fertile valleys, the region has been transposed into a sprawling urban metropolis. Early settlers, such as James Taylor Jr., Jacob Fowler, William Cave, and Thomas Kennedy knew well the potential of the incredibly beautiful territory they had discovered at the mouth of the Licking River. With the success of Newport on the Levee, rehabilitation projects in Covington's inner-core, and the explosion in residential construction and industrial expansion in the outlying cities, Northern Kentucky has developed into one of the most desirable places in the country for both new business and home ownership. This book provides a long-overdue, comprehensive history of the region. Concentrating on Boone, Bracken, Campbell, Carroll, Fleming, Gallatin, Grant, Kenton, Mason, Owen, Pendleton, and Robertson counties, the author chronicles the region from its first appearance above sea level to the growing suburbs of today. Making a way through time, the author locates key moments in history, such as the Battle of Blue Licks, the building of the Roebling Bridge, and the Beverly Hills Supper Club fire of 1977, and discusses how each shaped Northern Kentucky.--description provided by publisher.